A comparison of the effectiveness of amitriptilin and pregabalin treatment in fibromyalgia patients - Acet, Gunseli; Kaya, Arzu; Akturk, Semra; Akgol, Gurkan (Kare Publ, 2017)
OBJECTIVE: The present study is a comparison of the effectiveness of amitriptyline and pregabalin on the symptoms of fibromyalgia patients. METHODS: A total of 71 female patients aged >= 18 years were included in this study. The patients were divided into 2 groups. Pregabalin (n=36) or amitriptyline (n=35) treatment was initiated at daily oral dose of 450 mg and 25 mg, respectively for the indicated number of patients. The patients were evaluated at the start of treatment and at the end of 12 weeks. The Fibromyalgia Impact Questionnaire, Fatigue Severity Scale, Modified Fatigue Impact Scale, Hospital Anxiety Depression Scale, Nottingham Health Profile, Mini Mental State Test, and the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) were administered to all study participants. Pain at all tender points was measured using a pressure algometer. RESULTS: Significant improvement was observed in both groups after 12 weeks of treatment (p<0.05). Percent change in LANSS was greater in the pregabalin group compared with the amitriptyline group. Tender point pressure pain thresholds and total myalgic score improved significantly in both groups (p<0.05); however higher percentage change in these parameters was achieved in the amitriptyline group when compared with the pregabalin group (p<0.05). CONCLUSION: Both drugs improved pain, fatigue, sleep disorder, disability, psychological evaluation, and cognitive function; however, amitriptyline was more effective at reducing experimentally measured pain than neuropathic pain. According to these results, preference for pregabalin may be recommended in fibromyalgia patients whose primary complaint is neuropathic pain.
Keywords: Amitriptyline; fibromyalgia; neuropathic pain; pregabalin; pressure pain threshold